Incidence and Outcome of Vocal Cord Polyp: An Endoscopic Experience and Perception (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: vocal cord polyp; micro laryngeal surgery (MLS); gastroesophageal reflux disease (GERD)